BAHASA SUNDA DAN PENGGUNAANNYA DALAM INTERAKSI JUAL BELI DI PASAR SINDANG KABUPATEN CIREBON - Afi Fadlilah (SASDAYA: Gadjah Mada Journal of Humanities, 2016)
One dialect of Cirebon language is dialect Jawareh. It is the Java language which mix with Sundanese used in South of Cirebon regency, especially in Sindang Market on Lemahabang districts. This paper will discuss the language use in Sindang Market because it has its own characteristics that are different from the others Sundanese in West Java. This is because it is influenced by the geographical location and the diversity of backgrounds of the speech community. Based on this, this paper will discuss the Sundanese language and its use in the buying and selling interaction on the sindang market of Cirebon with the aim to describe the structure of the language and how to use it. The method used in this paper is the observational method with taping and recording techniques of the speech event data that is analyzed descriptively qualitative by using linguistic theory. The results of this study is that the specific characteristics of Sundanese in buying and selling interaction in the sindang market contained in intonation and the removal of vowel phonemes / a / and / ӧ / on specific vocabulary.